Eco-innovation strategies in hospitality: A case study of star-rated hotels in Batam - Zias Sathia; Dame Afrina Sihombing; Oda Ignatius Besar Hariyanto (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of eco-innovation on the sustainable performance of hotels in Batam, a destination characterized by a rapidly growing tourism and hospitality sector. Given the substantial environmental footprint of hotel operations through energy consumption and waste generation, understanding the effectiveness of different eco-innovation strategies is essential for advancing sustainability within the industry. Employing a quantitative research design, data were collected through surveys administered to managers of hotels that had been operating for at least ten years. A total of 120 valid responses were analyzed using Structural Equation Modeling with the Partial Least Squares approach through SmartPLS. The study evaluated four dimensions of eco-innovation: eco-product, eco-process, eco-organizational, and eco-marketing innovation. The findings reveal that eco-process, eco-organizational, and eco-marketing innovations exert significant positive effects on sustainable hotel performance, highlighting the importance of environmentally efficient operational practices, sustainability-oriented organizational systems, and green marketing initiatives in enhancing economic, environmental, and social outcomes. In contrast, eco-product innovation was not found to significantly influence sustainable performance, suggesting that environmentally friendly products alone may be insufficient to generate substantial sustainability improvements without complementary organizational and operational changes. These findings contribute to the literature on sustainable tourism and hospitality management by demonstrating the differentiated effects of eco-innovation dimensions on organizational sustainability. The study further suggests that future research should incorporate additional factors, such as green human resource management, green competitive advantage, and tourism development, to provide a more comprehensive understanding of sustainability drivers within the hotel industry. Keywords: Eco-Innovation; Sustainable Performance; Marketing Innovation; Organizational Innovation; Hospitality